2022
DOI: 10.3389/fbioe.2022.958381
|View full text |Cite
|
Sign up to set email alerts
|

Role of fibroblasts in wound healing and tissue remodeling on Earth and in space

Abstract: Wound healing (WH) and the role fibroblasts play in the process, as well as healing impairment and fibroblast dysfunction, have been thoroughly reviewed by other authors. We treat these topics briefly, with the only aim of contextualizing the true focus of this review, namely, the microgravity-induced changes in fibroblast functions involved in WH. Microgravity is a condition typical of spaceflight. Studying its possible effects on fibroblasts and WH is useful not only for the safety of astronauts who will fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 126 publications
1
71
0
1
Order By: Relevance
“…Fibroblasts have a crucial role in normal wound healing as they organize the whole repair process by producing regulatory molecules and crosstalk with the other types of cells involved in the healing mechanisms. 30 Previous studies have also shown the safety and non-toxicity of chlorogenic acid and polyvinyl alcohol. 31,32 These results could support the use of CGA hydrogel as a wound dressing.
Figure 4.Comparison of MTT cell viability on the NIH3T3 cell lines after exposure to different concentrations of CGA hydrogel after 24 h, 48 h and 72 h. The results are shown as the means ± SD ( n = 3).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibroblasts have a crucial role in normal wound healing as they organize the whole repair process by producing regulatory molecules and crosstalk with the other types of cells involved in the healing mechanisms. 30 Previous studies have also shown the safety and non-toxicity of chlorogenic acid and polyvinyl alcohol. 31,32 These results could support the use of CGA hydrogel as a wound dressing.
Figure 4.Comparison of MTT cell viability on the NIH3T3 cell lines after exposure to different concentrations of CGA hydrogel after 24 h, 48 h and 72 h. The results are shown as the means ± SD ( n = 3).
…”
Section: Resultsmentioning
confidence: 99%
“…Fibroblasts have a crucial role in normal wound healing as they organize the whole repair process by producing regulatory molecules and crosstalk with the other types of cells involved in the healing mechanisms. 30 Previous studies have also shown the safety and non-toxicity of chlorogenic acid and polyvinyl alcohol. 31,32 These results could support the use of CGA hydrogel as a wound dressing.…”
Section: Mtt Assessmentmentioning
confidence: 99%
“…The participation of fibroblasts in the healing process is critical since they are responsible for creating protein structural products that will be utilized throughout the tissue regeneration process. 11 Normal fibroblast division activity is limited, but when there is damage, these cells seem to be more active in creating extracellular matrix. Interleukin-Ib (IL-Ib), platelet-derived growth factor (PDGF), and fibroblast growth factor (FGF).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts are critical in supporting normal wound healing, involved in key processes such as breaking down the fibrin clot, creating new extra cellular matrix (ECM) and collagen structures to support the other cells associated with effective wound healing, as well as contracting the wound (Bainbridge, 2013). Healing problems such as fibrosis and delayed healing may occur if fibroblast dysfunction is present (Cialdai et al, 2022).…”
Section: Fibroplasiamentioning
confidence: 99%